Validate conference paper using dice coefficient. - Anuar, Nurhilyana; Md Sultan, Abu Bakar (Canadian Center of Science and Education (CCSE), 2010)
Dice Coefficient is the techniques to find similarity of an object and widely used in digital library, sciences and other fields. Thus, this project is the first attempts to employed Dice Coefficient for selecting paper in conference management system. An experimental result with limited test cases indicates Dice Coefficient is potentially to be used in the broad spectrum of respective application.